2014
DOI: 10.3109/10826084.2014.956365
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use and Antisocial Behavior in Adolescents: The Role of Family and Peer-Individual Risk and Protective Factors

Abstract: Extant literature reports a frequent co-occurrence of substance consumption and antisocial behaviors. It is also postulated, therefore, that risk and protective factors are shared by the two behaviors. The purpose of this research is to test this notion by exploring whether family and peer-individual risk and protective factors are similarly associated with unique and co-occurring substance consumption and antisocial behaviors. A sample of 1,599 school students ranging between the ages of 11 and 19 completed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
2
8
0
2
Order By: Relevance
“…This is consistent with results by Obando, Trujillo, and Trujillo (2014) and Yi et al (2011), who identified that protective factors have a smaller or inexistent effect on substance use among adolescents, as compared to risk factors. Current findings suggest that family attachment serves as a protective factor only through the reduction of negative emotional symptoms, which, as already mentioned, foster sensation seeking.…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with results by Obando, Trujillo, and Trujillo (2014) and Yi et al (2011), who identified that protective factors have a smaller or inexistent effect on substance use among adolescents, as compared to risk factors. Current findings suggest that family attachment serves as a protective factor only through the reduction of negative emotional symptoms, which, as already mentioned, foster sensation seeking.…”
Section: Discussionsupporting
confidence: 94%
“…Previous research had found that parental monitoring and responsiveness was associated with prosocial behaviors of the children (Obando et al, 2014; Slattery and Meyers, 2014; Bowker et al, 2016), in this investigation we had found that the principal aspect of parent-teenager exchanges was related to the presentation of a more varied behavioral repertoire by parents, corroborating our hypothesis about it.…”
Section: Discussionsupporting
confidence: 89%
“…It was found that the parental monitoring, conflictive family interactions, and low intimacy, were related with alcohol and drugs consumption (Obando et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…(Most research using data from the CTC youth survey has taken place in developed nations, including Australia, Canada, the Netherlands, the United Kingdom, and the United States [Arthur et al ; Beyers et al, ; Fairnington, ; Flynn, ; R. R. Glaser et al, ; Hemphill et al, ; Jonkman et al, ]. Recently the survey has also been administered in developing nations, with published research emerging from Colombia [Obando, Trujillo, & Trujillo, ], Croatia [Mihić, Novak, & Băsić, ], Iran [Baheiraei et al, ], Thailand [Wongtongkam, Ward, Day,. & Winefield, ], and Trinidad and Tobago [Katz & Fox, ; Maguire, ; Maguire, Wells, & Katz, ]).…”
Section: Measuring Family Risk and Protective Factorsmentioning
confidence: 99%
“…R. Glaser et al, 2005;Hemphill et al, 2014;Jonkman et al, 2005]. Recently the survey has also been administered in developing nations, with published research emerging from Colombia [Obando, Trujillo, & Trujillo, 2014], Croatia [Mihić, Novak, & Bȃsić, 2010], Iran [Baheiraei et al, 2014], Thailand [Wongtongkam, Ward, Day,. & Winefield, 2014], and Trinidad and Tobago [Katz & Fox, 2010;Maguire, 2013;Maguire, Wells, & Katz, 2011]).…”
Section: Measuring Family Risk and Protective Factorsmentioning
confidence: 99%